Design, implementation, and evaluation of an XG-PON module for the ns-3 network simulator. (May 2017) - Arokkiam, Jerome A; Alvarez, Pedro; Wu, Xiuchao; Brown, Kenneth N; Sreenan, Cormac J; Ruffini, Marco; Marchetti, Nicola; Doyle, Linda; Payne, David
10-gigabit-capable Passive Optical Network (XG-PON), one of the latest standards of optical access networks, is regarded as one of the key technologies for future Internet access networks. This paper presents the design and evaluation of our XG-PON module for the ns-3 network simulator. This module is designed and implemented with the aim to provide a standards-compliant, configurable, and extensible module that can simulate XG-PON with reasonable speed and support a wide range of research topics. These include analyzing and improving the performance of XG-PON, studying the interactions between XG-PON and the upper-layer protocols, and investigating its integration with various wireless networks. In this paper, we discuss its design principles, describe the implementation details, and present an extensive evaluation on both functionality and performance.